2013
DOI: 10.1080/21663831.2013.855272
|View full text |Cite
|
Sign up to set email alerts
|

Local Current-Activated Growth of Individual Nanostructures with High Aspect Ratios

Abstract: Supplementary Material Available OnlineThe development of vertical nanoelectronics is hindered by limited control over the growth of nanostructures in specific directions. A scanning tunneling microscopy tip was used as a guide to locally consolidate individual nanoparticles and grow metallic nanopillars with high aspect ratios. Consolidation from random agglomerates occurs through electromigration and diffusion in a temperature gradient. The results of this study provide a new avenue for the controlled growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In addition to the growth of oxide nanowires by mechanisms involving electromigration, interaction between atomic drift due to electric current and local temperature gradients resulting from intense Joule heating has been used to explain the growth of metal nanostructures as silver nanorods on a silver porous substrate. [58] Also electromigration in different experimental arrangements, has been proposed as a growth mechanism of tin whiskers, [59] nickel nano particles and nanopillars, [60] aluminum micro/nanowires, [61] or zinc nanowires. [62] Electromigration-induced plasticity was observed in Cu interconnect structures before the formation of voids and hillocks [63] and, in Cu strips [64] a tensile strain gradient from the cathode toward the anode during current stressing was found.…”
Section: Growth Of Oxide Nanowires and Other Structures During Joule Heating Of Metalsmentioning
confidence: 99%
“…In addition to the growth of oxide nanowires by mechanisms involving electromigration, interaction between atomic drift due to electric current and local temperature gradients resulting from intense Joule heating has been used to explain the growth of metal nanostructures as silver nanorods on a silver porous substrate. [58] Also electromigration in different experimental arrangements, has been proposed as a growth mechanism of tin whiskers, [59] nickel nano particles and nanopillars, [60] aluminum micro/nanowires, [61] or zinc nanowires. [62] Electromigration-induced plasticity was observed in Cu interconnect structures before the formation of voids and hillocks [63] and, in Cu strips [64] a tensile strain gradient from the cathode toward the anode during current stressing was found.…”
Section: Growth Of Oxide Nanowires and Other Structures During Joule Heating Of Metalsmentioning
confidence: 99%
“…This has been demonstrated in the case of Cu strips 23 where electromigration under high direct current was found to induce non-directional diffusion due to plastic deformation related to ions accumulation in certain regions, preferentially grain boundaries, with dislocations acting as easy diffusion path. Also electromigration has been proposed as the main growth mechanism of nanorods in porous silver 20 as well as individual nickel nanostructures 18 or Zn nanodots at a small tungsten tip in a transmission electron microscope. 19 Electromigration, which takes place inside the metal wire, would contribute to the formation of the oxide layer with micro and nanostructures by favoring diffusion processes towards the surface.…”
Section: Structures Formed On the Mo Wirementioning
confidence: 99%
“…It has been suggested that the rapid growth of undoped and doped MoO 3 plates 14 and ZnO nanowires 13 is related to thermally assisted electromigration which takes place in the metal wire during the ow of a high electric current density. Also, electromigration in temperature gradients has been considered as the mechanism to grow nickel nanopillars 18 Zn nanodots and nanowires 19 or silver nanorods. 20 In this work, the role of thermal effects and electromigration processes in the growth of a-MoO 3 nanoplates during Joule heating of Mo wires has been investigated by conducting the Joule heating experiments under an external electric eld perpendicular to the Mo wire by means of two parallel electrode plates.…”
Section: Introductionmentioning
confidence: 99%